2011
DOI: 10.3382/ps.2010-01057
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood and muscle samples to monitor for residues of the antibiotic enrofloxacin in chickens

Abstract: In 2005, the US Food and Drug Administration withdrew approval for use of enrofloxacin in poultry, thus effectively imposing zero tolerance for residues of this antibiotic in poultry. Conventional residue monitoring for most antibiotics, including enrofloxacin, involves removing poultry carcasses from the processing line and collecting muscle tissues for analysis. Because of the loss of valuable edible products and the difficulties and expense of sampling all the carcasses, only a small portion of carcasses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…The highest doxycycline concentration was observed in the liver, and similar results have previously been reported by other authors (2,11,15,34). In contrast to Reyes-Herrera et al (28), we observed only small differences between the enrofloxacin concentrations in the breast and thigh muscles. This discrepancy may be due to differences in the applied doses.…”
Section: Discussioncontrasting
confidence: 51%
“…The highest doxycycline concentration was observed in the liver, and similar results have previously been reported by other authors (2,11,15,34). In contrast to Reyes-Herrera et al (28), we observed only small differences between the enrofloxacin concentrations in the breast and thigh muscles. This discrepancy may be due to differences in the applied doses.…”
Section: Discussioncontrasting
confidence: 51%
“…and consequently increase the infection rate in humans [41]. Because of this, the FDA imposed a zero-tolerance policy for residues of enrofloxacin and ciprofloxacin in broilers, with the target tissue used for monitoring these residues being muscle; this is the tissue with the greatest antibiotic concentration and persistence, with the highest concentration of residues found in the breast muscle [11]. …”
Section: Resultsmentioning
confidence: 99%
“…However, most published studies that have evaluated the pharmacokinetics or the withdrawal period of enrofloxacin in broiler chickens used microbiological assays [9–11] or high-performance liquid chromatography (HPLC) methods [1214]. These studies also did not employ the quantitative and confirmatory methods recommended by regulatory agencies for the study of veterinary drugs in animal tissues, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to treat specific infections and against a broad spectrum of Gram-negative and Gram-positive bacteria in both stationary and growth phases of bacterial replication (Scheer, 1987). Its wide in vivo distribution, unique antimicrobial effect, high bioavailability, less toxicity, and side effects, make it one of the most commonly used antibiotics for treatment of various animal infectious diseases, and a desirable antibiotic choice for difficult-to-treat infections, particularly those that need long-term antibiotic treatment (Divers et al, 2008;Ebert et al, 2011;Reyes-Herrera et al, 2011;Jerjomiceva et al, 2014;Lin et al, 2014;Rico et al, 2014;Andrieu et al, 2015;Nguyen Dang Giang et al, 2015;Phillips et al, 2015;Piras et al, 2015;Carrascosa et al, 2017;Foster et al, 2017;Roth et al, 2017;Strze R pa et al, 2017;Zhu et al, 2017;Rico et al, 2018). The bactericidal activity of enrofloxacin is concentration-dependent, with susceptible bacterial cell death occurring within 20-30 minutes of exposure.…”
Section: Introductionmentioning
confidence: 99%